Experimental investigation on the thermal characteristics and grey correlation analysis of frost penetration depths for different subgrade soils - Firat, Muge Elif Orakoglu (Springer, 2021)
In this study, thermal characteristics of the subgrade soils (well-graded sandy soil, low-plasticity clayey soil and low-plasticity silty soil) were tested by a KD2-Pro Thermal Properties Analyzer. Then, frost penetration depths have been predicted by modified Berggren equation for a subgrade section considering climatic conditions of Turkey's geographic regions. Experimental results showed that the thermal conductivity is maximum for the well-graded sandy soil and the minimum values were determined for the low-plasticity silty soil. The highest values of heat capacity, thermal diffusion and thermal resistance have been measured for the low-plasticity clayey soil and minimum values of the heat capacity, thermal diffusion and thermal resistance were observed on the well-graded sandy soil specimens. The maximum frost penetration depths were predicted for the well-graded sandy soil specimens and the minimum frost penetration depths were observed on the low-plasticity clay soils due to water holding capacity and high insulation of clay. In addition, the Gray correlation analysis was utilized to present the correlation degree between the frost penetration depths and different parameters including thermal characteristics, average annual temperatures, number of days covered snow, surface freezing index, and correction factors. Results showed that the thermal characteristic has more influence than other parameters on the frost penetration depths.
Keywords: Frost penetration depth; Subgrade soil types; Modified Berggren equation; Gray correlation analysis